2021
DOI: 10.1016/j.jcot.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Reverse total shoulder arthroplasty for irreparable rotator cuff tears without arthritis: A systematic review

Abstract: Introduction: Indications for reverse total shoulder arthroplasty (RTSA) have expanded over recent years. Whilst cuff tear arthropathy is an accepted indication, the results of its use in those without arthritis is not clear. The aim of this article is to review the literature on RTSA for massive rotator cuff tears without associated arthritis. Methods: A systematic review search was performed in accordance with Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines to find all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Ernstbrunner et al reported that improvement in shoulder scores may be sustained over 10 years in the presence of massive tears; however, survivorship was 85% at 5 years and 70% at 15 years [ 97 ]. Other series demonstrate a sustained improvement in shoulder scores and a lower incidence of complications in the absence of glenohumeral osteoarthritis; however, these remain a concern [ 98 , 99 ]. The National Joint Registry of England, Wales and Northern Ireland report a risk of revision of 3.85% at 8 years in all patients who receive a RSA, with a median patient age of 76 years [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ernstbrunner et al reported that improvement in shoulder scores may be sustained over 10 years in the presence of massive tears; however, survivorship was 85% at 5 years and 70% at 15 years [ 97 ]. Other series demonstrate a sustained improvement in shoulder scores and a lower incidence of complications in the absence of glenohumeral osteoarthritis; however, these remain a concern [ 98 , 99 ]. The National Joint Registry of England, Wales and Northern Ireland report a risk of revision of 3.85% at 8 years in all patients who receive a RSA, with a median patient age of 76 years [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it was designed and advocated for use in Cuff Tear Arthropathy, the reliability of outcomes from this technique has seen its indications extend to patients with rotator cuff tears, with no arthritis. 15 Some of the risks associated with RSA are significant, and hence this will remain a reliable option for the elderly or those who have exhausted all the other options.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…In addition, there is a 10% to 33% repair rate for the life of such implants, and complications increase with each repair. [10,11] Therefore, it is difficult for surgeons are working hard to develop new surgical methods to treat IRCTs.…”
Section: Introductionmentioning
confidence: 99%
“…A recently popular approach to IRCTs is reverse total shoulder arthroplasty (RTSA), where RTSA allows the deltoid to replace the muscle of IRCTs and has shown good results in multiple trials. [10] This technique has been used in patients with significant glenohumeral arthritis, anterior superior escape, and/or pseudoparalysis. However, although complications after RTSA have improved, 20% to 50% of complications have been reported in a recent study.…”
Section: Introductionmentioning
confidence: 99%